2017
DOI: 10.14785/lymphosign-2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell transplantations for primary immune deficiencies associated with NFκB mutations: A review of the literature

Abstract: The nuclear factor kappa-light-chain-enhancer of activated B-cells (NFκB) family of transcription factors plays an instrumental role in human immunity and lymphoid organ development. Inherited defects affecting these factors or their regulation are associated with increased susceptibility to infections, as well as non-immune abnormalities. Hematopoietic stem cell transplantations (HSCT) have been shown to correct the immune abnormalities in a few patients with NFκB pathway defects. Here we review the pre-HSCT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
(54 reference statements)
1
2
0
Order By: Relevance
“…In addition, 2 previously unaffected children had de novo inflammatory bowel disease after HSCT. 83 These findings mirror those reported elsewhere in human subjects, 82 as well as in mice, which is suggestive of a robust immune response to intestinal bacteria after acquisition of a competent immune system. 84 With respect to conditioning, a recent review demonstrated that in 5 children with XL-EDA-ID who received reduced-intensity conditioning, 3 did not engraft after first HSCT, and 1 more did not show T-cell engraftment.…”
Section: Treatment Considerations For Nf-kb Pathway Defectssupporting
confidence: 85%
See 1 more Smart Citation
“…In addition, 2 previously unaffected children had de novo inflammatory bowel disease after HSCT. 83 These findings mirror those reported elsewhere in human subjects, 82 as well as in mice, which is suggestive of a robust immune response to intestinal bacteria after acquisition of a competent immune system. 84 With respect to conditioning, a recent review demonstrated that in 5 children with XL-EDA-ID who received reduced-intensity conditioning, 3 did not engraft after first HSCT, and 1 more did not show T-cell engraftment.…”
Section: Treatment Considerations For Nf-kb Pathway Defectssupporting
confidence: 85%
“…In this regard outcome studies show considerable variability depending on the underlying disease process, as well as transplant factors, such as choice of conditioning. 82,83 To date, the majority of experience has been described in patients with NEMO defects. A recent HSCT study in 29 patients with XL-EDA-ID showed 74% survival within a median followup period of 57 months.…”
Section: Treatment Considerations For Nf-kb Pathway Defectsmentioning
confidence: 99%
“…Nevertheless, post-HCT IBD symptoms were found in some patients with IPEX syndrome, suggesting the complex etiology underlying intestinal inflammation that could not be completely managed by the rescue of T regs after HCT [7,31]. Among PIDs due to defects in the CBM signaling complex and NF-κB pathway, early-onset IBD (EO-IBD) has been uncontrollable in patients with NEMO deficiency after HCT [32,33]. IBD in MALT1-deficient patients has been shown to be well controlled after HCT; however, IBD in MALT1 deficiency needs careful pre-transplant assessment.…”
Section: Casementioning
confidence: 99%